Machine gun the development of the machine gun from the nineteenth century to the present day - Popenker, Maxim; Williams, Anthony G., 1949- (The Crowood Press, 2008)
With a country-by-country breakdown of machine guns, including comprehensive appendices of gun and ammunition data, along with hundreds of photographs, this is a comprehensive study of a most effective battlefield weapon.